Russian Composers Abroad : How They Left, Stayed, Returned - Dubinet︠s︡, Elena Aleksandrovna, 1969- (Book collections on Project MUSE., 2021)
"As waves of composers migrated from Russia in the 20th century, they grappled with the complex struggle between their own traditions and those of their adopted homes. Russian Composers Abroad explores the self-identity of these emigres, especially those who left from the 1970s on, and how aspects of their diasporic identities played out in their music. Elena Dubinets provides a journey through the complexities of identity formation and cultural production under globalization and migration, elucidating sociological perspectives of the post-Soviet world that have caused changes in composers' outlooks, strategies, and rankings. Russian Composers Abroad is an illuminating study of creative ideas that are often shaped by the exigencies of financing and advancement rather than just by the vision of the creators and the demands of the public"--